Who Values Education? Socio-Demographic Predictors of Educational Attitudes in the Philippines - Ianne Calica (Indonesian Journal of Educational Research and Review, 2026)
Educational equity requires attention not only to formal access but also to social values that shape how families and communities perceive educational opportunity. This study examined socio-demographic predictors of educational values in the Philippines, focusing on concern about providing quality education for children and agreement with the belief that university education is more important for boys than for girls. A quantitative cross-sectional design was applied using secondary data from the World Values Survey Wave 7 Philippines. The study analyzed a weighted sample of 1,200 adult respondents selected through a multi-stage probability sampling design across major Philippine regions. Data were analyzed through descriptive statistics, Chi-square tests, and binary logistic regression. The findings showed that 11.2% of respondents expressed serious concern about providing quality education, while 44% agreed that university education is more important for boys. Bivariate analysis indicated significant associations between educational concern and marital status, age, and religion. Gendered university attitudes were significantly associated with marital status, age, religion, sex, educational attainment, urban-rural residence, and settlement type. Regression results confirmed that marital status, religion, and settlement type predicted educational concern, whereas sex, educational attainment, religion, and settlement type predicted male-priority attitudes. The study highlights the need for culturally responsive educational policies.